Preliminary study on the cooling effect of geothermal exchange at the superficial layer on greenhouse in South Jiangsu in summer - WANG Jiawei; WANG Zhao; YANG Junwei; ZHAO Hailiang; ZOU Zhirong (浙江大学学报. 农业与生命科学版)
The area of facility agriculture in China ranks forefront in the world. In recent years, as an emerging technology of environmental management inside the greenhouse, ground source heat pump (GSHP) is sufficiently emphasized by many scholars. While most of them only focus on heating effect of greenhouse rather than its cooling effect, due to some severe crop problems induced by relatively high temperature in South Jiangsu during summer. In this study, some related indexes were analyzed from the perspective of cooling effect, and the effectiveness and practicability of the cooling system were evaluated in the experimental greenhouse.The experiment was conducted in two plastic greenhouses in Zhangjiagang City from May 5 to July 17, 2016. The greenhouses were located from north to south, with 88 m long, 7 m wide, and 3 m high, which were assembled with steel tubes and ethylene vinyl acetate (EVA) films. Two greenhouses with similar external environmental conditions and specifications were selected for treatment and control sets, respectively. The air inlet was set at the ridge and the air outlet was on the west side of greenhouse with 20 cm vertical distance from the ground. The buried depth of pipe processing heat exchange in the treatment greenhouse was 60 cm, including 14 groups of polyvinyl chloride (PVC) pipes with the diameter of 110 mm. With 160 W of the input power, 0.2 m3/s of the measured air quantity, and 40 r/s of the rotation, the fan was turned on at 6:00 a.m. and turned off at 6:00 p.m. in the same day. The bottom ventilation was set at 80 cm from east and west side along the greenhouses. The greenhouses were planted with watermelon and ventilated normally from 6:00 a.m. to 6:00 p.m. every day without using sunshade net. The ambient temperature and humidity, and the soil temperature at 60 cm, 40 cm and 15 cm were tested, and the processing humiture at inlet and outlet of heat exchange pipe of greenhouse was calculated at a 10-minute frequency. Then enthalpy difference, heat accumulation capacity, average heat flux, average density of heat flow, and energy efficiency and consumption were analyzed.The result indicated that from May 5 to July 17, the average temperature reduction in the treatment greenhouse with heat exchange pipe was 3.4℃ in sunny days, 1.5℃ in cloudy days and 0.8℃ in rainy days, compared with the control without heat exchange pipe. The change in humidity was comparatively insignificant between the treatment and control, which were both 40%-90% in sunny days, 60%-100% in cloudy days, and 80%-100% in rainy days. In three continuous sunny days, the ground temperature at the depth of 60 cm was basically at the constant temperature of 21.3℃ in the control greenhouse, and it fluctuated at 21.8 ℃±0.4℃ in the treatment greenhouse; the average daily temperature at the depth of 40 cm was basically at 22.7 ℃, rising at 0.1 ℃/d for the control, and it was 23.9 ℃, rising at 0.4 ℃/d in a wave mode for the treatment; the average daily temperature at the depth of 15 cm was basically at 24.8℃ for the control, and it was 25.7 ℃, rising at 0.5 ℃/d in a wave mode for the treatment. In heat exchange, enthalpy difference was 0.166-9.560 kJ/kg; the heat accumulation capacity was 3.94×105 kJ; the daily electricity consumption was 0.8×105 kJ, and the coefficient of performance (COP) was 4.21 in the treatment greenhouse. Compared with the investment cost of air condition (AC) with the highest energy efficiency standard, the investment cost of the shallow geothermal exchange system was only 15.5% and the energy consumption ratio was 1.4 times higher than that of AC.Therefore, we conclude that the cooling effect using the heat exchange system at superficial layer is significant and promising in south Jiangsu in summer.